Distributed Fault-Tolerant Event Region Detection of Wireless Sensor Networks - Dyi-Rong Duh; Ssu-Pei Li; Victor W. Cheng (International Journal of Distributed Sensor Networks)
This work provides a distributed fault-tolerant event region detection algorithm for wireless sensor networks. The proposed algorithm can identify faulty and fault-free sensors and ignore the abnormal readings to avoid false alarm. Moreover, every event region can also be detected and identified. Simulation results show that fault detection accuracy (FDA) is greater than 92%, false alarm rate (FAR) is near 0%, and event detection accuracy (EDA) is greater than 99% under uniform distribution. FDA is greater than 92%, FAR is less than 1.2%, and EDA is greater than 88% under random distribution when sensor fault probability is less than 0.3.